2021
DOI: 10.1021/acs.joc.1c00288
|View full text |Cite
|
Sign up to set email alerts
|

Application of 1,4-Oxazinone Precursors to the Construction of Pyridine Derivatives by Tandem Intermolecular Cycloaddition/Cycloreversion

Abstract: This study reveals a new method for the preparation of 1,4-oxazinone derivatives by Staudinger reductive cyclization of functionalized vinyl azide precursors. The resulting oxazinone derivatives prepared in this manner were intercepted with terminal alkyne substrates through an intermolecular cycloaddition/cycloreversion sequence to afford polysubstituted pyridine products. Alkyne substrates bearing propargyl oxygen substitution showed good regioselectivity in the cycloaddition operation selectively affording … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Oxazinone 6 and the symmetric TMS-bisalkyne 10a were reacted overnight in toluene at 110 °C (entry 1). We noticed that this thermal cycloaddition/cycloreversion reaction had a faster rate relative to other precursors previously explored 3 5 and the resulting product 11a was afforded in excellent yield (96%) as a single pyridine isomer. 8 In similar fashion, the bispropargyl ether 10b was also effective in the reaction sequence and gave pyridine 11b in 46% yield and as a 19:1 ratio of isomers (entry 2).…”
Section: Table 1 3-alkynyl Pyridines From Oxazinones An...mentioning
confidence: 81%
See 1 more Smart Citation
“…Oxazinone 6 and the symmetric TMS-bisalkyne 10a were reacted overnight in toluene at 110 °C (entry 1). We noticed that this thermal cycloaddition/cycloreversion reaction had a faster rate relative to other precursors previously explored 3 5 and the resulting product 11a was afforded in excellent yield (96%) as a single pyridine isomer. 8 In similar fashion, the bispropargyl ether 10b was also effective in the reaction sequence and gave pyridine 11b in 46% yield and as a 19:1 ratio of isomers (entry 2).…”
Section: Table 1 3-alkynyl Pyridines From Oxazinones An...mentioning
confidence: 81%
“…The greater reactivity of oxazinones enables reaction in both the inverse- and normal-electron-demand Diels–Alder modes; unactivated or electron-deficient alkynes represented by 2 may serve as the 2π reaction component. 3 The resulting [2.2.2]bicycloadducts 3 are generally not stable and undergo facile extrusion of CO 2 . In this way, pyridine products resembling 4 may be obtained in some cases at ambient temperatures.…”
Section: Table 1 3-alkynyl Pyridines From Oxazinones An...mentioning
confidence: 99%
“…We viewed the guaipyridine scaffold as an instructive model to explore our interest in the de novo synthesis of pyridines by domino reaction processes. 15 16 We saw an opportunity to advance new chemistry and explore the reactivity and selectivity of an oxazinone precursor in a cycloaddition/cycloreversion sequence. Our synthesis plan highlighted in Scheme 1 targeted rupestine L and M as our entry point to the guaipyridine alkaloid core.…”
mentioning
confidence: 99%
“…General substructure analysis of the requisite oxazinone precursor 11 revealed that both 11 and 9 are at the same oxidation state and thus potential access might be achieved starting from acetylenedicarboxylate 9 . Methods to prepare oxazinones have been summarized elsewhere, 15 but the synthesis of oxazinone 11 from 9 was not known and would thus represent a new method to rapidly construct functionalized oxazinone precursors. Moreover, oxazinone 11 , which possesses a functional group (CO 2 R) at the position that corresponds to the oxygenated C8 position, could enable construction of target natural products 7 and 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation